Methodological Approaches to Measuring Dental Surgeons’ Workload in Surgical Practice - Savchuk, O.; Rozhko, M.; Stupnytsky, R. (Actual Dentistry, 2025)
Abstract. The advancement of medicine, particularly in dentistry, is a key factor in ensuring the delivery of quality healthcare. The implementation of innovative technologies and research methodologies contributes to the improvement of healthcare systems in Ukraine. One of the criteria for evaluating dental care quality is the duration of procedures, assessed through time standards and conditional labor intensity units. For the objective determination of such indicators, an officially approved methodological framework is necessary. In 1999, Ukraine implemented a labor standardization methodology that became the foundation for evaluating the efficiency of dental practitioners. Regular review and updating of these methodologies is essential for integrating global experience and ensuring compliance with contemporary standards. Based on the data above, this research aims to enhance the efficiency of dental care provision to the Ukrainian population by developing methodological provisions for a unified system of assessment, accounting, and monitoring of dental surgeons’ work during surgical appointments. To achieve this goal, several objectives were established, with the primary one being the creation of fundamental methodological provisions that ensure objectivity and accuracy in the process of accounting, assessment, and monitoring of oral surgeons’ work. The time standard (TS) for providing surgical care is determined as the sum of permanent (Tp) and variable-repeatable (Tvr) time expenditures, specifically: TS = Tp + Tvr. This approach enables the establishment of individual standards for each type of dental intervention, ensuring accuracy, efficiency, and adherence to contemporary quality standards for medical care. Subsequently, after establishing the necessary TS indicators, a methodology is applied to determine labor expenditures specifically for surgical appointments. This approach utilizes a formula for determining conditional labor intensity unit (CLU) indicators in absolute numbers: CLU = Tts/T1CLU . The conclusions highlight the importance of standardizing all types of surgical dental care, including the implementation of digital protocols. Methodological measures aimed at determining labor expenditures are optimal for oral surgery.